Why is Instagram so Popular in Indonesia? Global Communication Features on Online Interaction - Aryati Hamzah; Siti Afrianty H Kundji; Rahayu Agustina Ishak; Nursapitri Djarati; Arfan Nagaring (Journal of Governance and Global Studies, 2025)
Instagram is an application that allows users to share photos and videos. Instagram also offers features that allow users to interact with other people online. It is one of the most popular social media apps in the world and has been increasing in popularity in recent years. Instagram features include: Photo and Video Sharing: Users can share photo and video content with other users. Interact with Other Users: Users can follow other accounts, leave comments, and "like" other people's content. Follow Most People: Users can follow others and view the content they share. Follow Trends: Users can follow popular topics or emerging trends. Collaborate: Users can collaborate with other users to create interesting content. Create a Business Account: A business account allows users to sell products online. Instagram Stories: This feature allows users to share photo and video content that can only be viewed for 24 hours. Instagram Live: This feature allows users to broadcast live videos and interact with other users. Instagram Shopping: This feature allows users to buy products through Instagram. Instagram Ads: Users can promote their content with ads displayed on Instagram. Instagram Reels: This feature allows users to create short videos and edit them with various effects and filters. Instagram Direct: This feature allows users to send messages to other users privately. Instagram Insights: This feature allows users to view their account analytics and see how their content is being received by their audience.